Copa do Mundo Fifa - Brasil 2014: realidades, mitos e legados na cidade de São Paulo - Rossetto Júnior, Adriano José (2016)
The mega sporting events are, in principle, described as a opportunity to stimulate and boost the sport in the country, a window of opportunity for sports development. In this way, includes-if the educational sport, ensuring the right of sports to all citizens as promulgates the National Constitution of 1988. The objective this thesis was to evaluate the legacy of 2014 FIFA World Cup for educational sport in São Paulo city, identifying, mapping, analyzing and classifying public policies, programs and sports projects developed by the Municipal Secretary of Sports and Leisure of São Paulo (MSSL). The research employed a qualitative approach case study, choosing the educational sport in São Paulo city as the focus. Initially, it undertook a literature review on the theories sociological of Norbert Elias and Pierre Bourdieu and its links with the sociology of sport, in Preuss's study of the legacy of mega sporting events and in Marx's theory about the relation of sport as a commodity. Later a documentary analysis was held, in search of primary sources, leaning up on the Guidelines and Budget Laws of the City and documents of MSSL to analyze the public sports policies, while observing the budgets, programs, projects and sports events realized by MSSL in São Paulo, during the administration of mayors Kassab (2009-2012) and Haddad (2013-2016). Also, there were qualitative interviews with nine employees and former employees of MSSL as a way of getting information that could demonstrate the sports policies of both administrations and the legacy into the organization of FIFA's World Cup - Brazil 2014 into city sports. It was found that during Haddad's management there was a reduction of investments in sport, of activities and also related to the numbers of calls in the projects and programs of the MSSL. As a result we see a shrinkage in the workforce and in the equipments, public sports structures worn and without magnification. Thus, as a positive legacy of the FIFA's World Cup to the sport in São Paulo city was only the new Arena, since the impact on educational sport was negative, with the decadence of School's Club Program. The huge winners of the legacy are the actors who holds more power in the Municipal sports field, ie, politicians, businessmen, show managers who defend the highperformance sports or commodity in fact, the accumulation and capital rise. The MSSL languishes, educational and leisure sport in the largest host cities of the country agonizes which demonstrate that the realization of mega sporting events does not require obligatorily and directly a legacy for sport